Emergence of mucormycosis following second wave of COVID-19 pandemic and possible risk factors in a hilly state of North India - Sharma, Kamlesh; Sharma, Ram Lal; ., Sunita (International Journal Of Community Medicine And Public Health, 2022)
Background: Mucormycosis is a rare, highly aggressive fungal infection affecting the rhino-orbital, respiratory, gastrointestinal or cutaneous systems and is caused by a group of moulds called mucoromycetes belonging to order Mucorales and has been associated with corona pandemic. The aim of the study was to assess the emerging trends of mucormycosis following second wave of Corona pandemic and possible risk factors in a hilly state of North India. Methods: It was a retrospective data analysis study where the information’s were gathered from various sources in state of Himachal Pradesh. After detection of 1st case, data was collected from May 2021 to July 2021. Since objective and authentic data was released by different agencies daily, so the state profile of mucormycosis cases was taken as per information available from newspapers, various state websites and analysed for various parameters. Results: The current study conducted in state of Himachal Pradesh showed that Hamirpur was the worst hit district with affected population 0.002%, with case fatality rate 57%. While male mortality was more (60%) as compared to female mortality (40%). Conclusions: This study showed that underlying risk factors for mucormycosis were COVID-19 infection, un-controlled diabetes, steroid and oxygen use.